The National Accreditation System for Higher Education Institutions in Russia; Higher Education in Europe; Vol. 27, № 3 - Pokholkov Y. P. Yuri Petrovich (2002, 2002)
The national accreditation system for higher education institutions in the Russian Federation is presented. The procedure for the integrated assessment of university activities, which is provided by the Ministry of Education, is described. The article examines licensing and attestation requirements and the procedure for achieving state accreditation. The requirements for gaining public professional accreditation are examined, as well as the tasks of the Russian Association for Engineering Education in this field. The experience of Tomsk Polytechnic University in developing an internal attestation system and quality assurance for its educational process is discussed, as well as the involvement of the institution in international co-operation